BRIDGING CULTURES: INTERCULTURAL COMMUNICATION IN PUBLIC RELATIONS FOR JAKARTA PRACTITIONERS - Irmulansati Tomohardjo; Mokhtarrudin Ahmad; Haekal Fajri Amrullah (Profetik: Jurnal Komunikasi, 2023)
This research aims to describe how public relations practitioners apply intercultural communication competence, who have worked in government institutions, mass media, hospitality, and other organizations with a diversity of ethnic and cultural members, and also should have specific competence to solve their problem communication in all daily activities. This research is based on an intercultural communication perspective, and interpersonal competence of public relations, with the research method being a case study, interviewing technique for gathering data, and qualitative descriptive analysis.Five key informants invited with different background organizations described that they have worked in public relations functions and follow the mechanism of intercultural communication competencies, such as motivation to communicate, sufficient knowledge of culture, appropriate communication skills, sensitivity, and character. The research result describes five competencies that have applied in their professional communication activities,  especially building good relationships, mapping cultural background, having a high motivation to communicate with others, practicing relevant communication when they encounter several difficulties, then always trying to understand the psychology of others when they start to communicate, in formal or informal situation. Then, in the process of anticipating so as not to experience frustration or culture shock with communication partners from different cultures, the speakers also made adaptations, making relevant adjustments, based on the current situation, in the form of speaking in general, discussing local products, discussing the latest issues. and optimize social media. It becomes a medium to reduce the inconvenience of communicating due to differences in culture and background.